2021
DOI: 10.21203/rs.3.rs-228960/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expression of SARS-CoV-2-related Receptors in Cells of the Neurovascular Unit: Implications for HIV-1 Infection

Abstract: Background. Neurological complications are common in patients affected by COVID-19 due to the ability of SARS-CoV-2 to infect brains. While the mechanisms of this process are not fully understood, it has been proposed that SARS-CoV-2 can infect the cells of the neurovascular units (NVU), which form the blood-brain barrier (BBB). The aim of the current study was to analyze the expression pattern of the main SARS-CoV-2 receptors in naïve and HIV-1-infected cells of the NVU in order to elucidate a possible pathwa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 95 publications
3
19
0
Order By: Relevance
“…In the present study we have investigated the molecular indices of Neuro-COVID-19 as they are related to brain endothelial cells forming the BBB. Despite our previous observation that primary HBMECs express several receptors for the virus (Torices et al, 2021), we found little to no indication of productive viral replication in the supernatants of HBMECs which is in accordance with previous reports that described that several endothelial cell types are not permissive for SARS-CoV-2 productive infection (McCracken et al, 2021; Nascimento Conde et al, 2021). Krasemann et al, (2022) observed infection of iPS-derived HBMECs but only at MOIs 10 and 100, which are unlikely to have pathological significance.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study we have investigated the molecular indices of Neuro-COVID-19 as they are related to brain endothelial cells forming the BBB. Despite our previous observation that primary HBMECs express several receptors for the virus (Torices et al, 2021), we found little to no indication of productive viral replication in the supernatants of HBMECs which is in accordance with previous reports that described that several endothelial cell types are not permissive for SARS-CoV-2 productive infection (McCracken et al, 2021; Nascimento Conde et al, 2021). Krasemann et al, (2022) observed infection of iPS-derived HBMECs but only at MOIs 10 and 100, which are unlikely to have pathological significance.…”
Section: Discussionsupporting
confidence: 90%
“…In the same context, HBMECs infected with different MOIs did not show any increase in the expression of SARS-CoV-2 Spike1 and E genes at 6 and 24 hpi ( Figure 1B ). We showed recently that HBMEC cells express, to some extent, several of SARS-CoV-2 receptors at both RNA and protein levels (Torices et al, 2021). Therefore, we evaluated the possible effect of infection on the expression of ACE2 and TMPRSS2 in HBMEC cells and found that infection with the MOI 0.1 induced a 40% decrease in ACE2 mRNA expression (p<0.05), which did not result in ACE2 protein level alterations ( Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At least two risk factors are believed to contribute to the CNS vulnerability to SARS‐CoV‐2: direct viral invasion and infection of CNS cells (Cantuti‐Castelvetri et al, 2020; Meinhardt et al, 2021) and indirect immune response from peripheral infection (Pellegrini et al, 2020; Yang et al, 2021), both of which are tightly associated with glial‐mediated CNS immunity. Indeed, multiple evidence exist confirming the expression of angiotensin‐converting enzyme 2, the receptor for the spike protein of SARS‐CoV‐2 in astrocytes and microglia (Chen et al, 2021; Gowrisankar & Clark, 2016; Hernández et al, 2021; Torices et al, 2021). Experimental studies have shown that the spike protein of SARS‐CoV‐2 is able to trigger immune responses in macrophage and microglia (Frank et al, 2022; Shirato & Kizaki, 2021; Zhao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 enters the cells through the angiotensin-converting enzyme-2 receptors (ACE2-R). The expression of ACE2-R is markedly upregulated on activated type 1 macrophages such as alveolar macrophages, Kupffer cells within liver, and microglial cells in brain [58][59][60]. Microglial cells are known to participate to the transport of SARS-CoV-2 to the brain [61].…”
Section: Primo-infection Of Covid-19 and Microgliamentioning
confidence: 99%